ETNOBOTANI MARSIDUDU PADA MASYARAKAT SUB ETNIS BATAK MANDAILING DI PASAR SANGKUMPAL BONANG KOTA PADANGSIDIMPUAN [Ethnobotanical Of Marsidudu In Sub ethnic Batak Mandailing Communities At Sangkumpal Bonang Market Padangsidimpuan City] - Revis Asra; Anita Rahmadhani Batubara; Ahmad Sazali (BRIN Publishing (Penerbit BRIN), 2023)
Marsidudu is a traditional steam bath tradition performed by the Mandailing Batak sub-ethnic group. This research was conducted to determine the knowlodge of the Mandailing Batak ethnic community about the marsidudu tradition. Data collection was carried out through in dept interview. The results of the study show that the Mandailing Batak ethnic community utilizes 29 types of plants used for the marsidudu tradition. The perceived benefits of marsidudu are refreshing the body, relieving muscle pain, relieving stress, relieving aches, improving blood circulation and the body feeling more fragrant and having bright vision. In the process of carrying out this marsidudu there are 3 stages, namely boiling the ingredients, carrying out marsidudu and after doing marsidudu. The results of quantitative data analysis showed that Nypa fructicans was the type of plant that had the highest ICS value of 600. The part of the plant that was most used for marsidudu was the leaves (52,7%).